2016
DOI: 10.22621/cfn.v130i2.1846
|View full text |Cite
|
Sign up to set email alerts
|

Climate Warming as an Explanation for the Recent Northward Range Extension of Two Dragonflies, <i>Pachydiplax longipennis</i> and <i>Perithemis tenera</i>, into the Ottawa Valley, Eastern Ontario

Abstract: (1) the climate in the newly occupied territory has warmed sufficiently to allow colonization; (2) a new range expectation based on the amount of climate warming is met; (3) other factors potentially promoting spread are excluded; (4) the possibility that range extension is a result of difficulty of observation and/or insufficient fieldwork in earlier times is excluded; (5) there is ample evidence for establishment; and (6) spread has been in the direction of the warmer territory or within it. By 2000, the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The possibility of change in lichen communities in response to a warming climate has been of interest since van Herk et al (2002) related rising temperature to increases in "warmth-loving" species and declines in "boreo-alpine" species in the Netherlands. Although the rise in average temperature reported there (0.8°C) was comparable to the 1°C rise recorded in Ottawa (Catling 2016), an increase that was regarded to be sufficient to explain the northern range extension of two dragonflies (Catling 2016), we have not observed such changes in the lichen biota.…”
Section: Lichens and Climate Changesupporting
confidence: 47%
“…The possibility of change in lichen communities in response to a warming climate has been of interest since van Herk et al (2002) related rising temperature to increases in "warmth-loving" species and declines in "boreo-alpine" species in the Netherlands. Although the rise in average temperature reported there (0.8°C) was comparable to the 1°C rise recorded in Ottawa (Catling 2016), an increase that was regarded to be sufficient to explain the northern range extension of two dragonflies (Catling 2016), we have not observed such changes in the lichen biota.…”
Section: Lichens and Climate Changesupporting
confidence: 47%
“…The existing body of scientific literature that has specifically assessed climate variability for Ottawa, Ontario, Canada, and surrounding area, is limited (e.g., [14][15][16][17][18]). Of these studies, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Of these studies, ref. [18] focused less directly on climate trends and more on the effect of general Environments 2022, 9, 35 2 of 32 climate warming as a possible influence on insect populations in the Ottawa area. The other studies variously noted trends such as an increase in wet and humid conditions [14]; seasonal increases in daily minimum temperature values, as well as seasonal variation in daily maximum temperature trends [17]; the attribution of the urban heat island effect as a cause of observed winter warming in Ottawa when contrasted with smaller surrounding communities [15]; and decreased fluvial discharge throughout the Ottawa area [16].…”
Section: Introductionmentioning
confidence: 99%
“…The existing body of scientific literature that has specifically assessed climate variability for Ottawa, Ontario, Canada, and surrounding area, is limited (e.g. (Bootsma, 1994); (Prokoph and Patterson, 2004); (Adamowski and Prokoph, 2013); (Ahmed et al, 2014); (Catling, 2016)). Of these studies, (Catling, 2016) focused less directly on climate trends and more on the effect of general climate warming as a possible influence on insect populations in the Ottawa area.…”
Section: Introductionmentioning
confidence: 99%
“…(Bootsma, 1994); (Prokoph and Patterson, 2004); (Adamowski and Prokoph, 2013); (Ahmed et al, 2014); (Catling, 2016)). Of these studies, (Catling, 2016) focused less directly on climate trends and more on the effect of general climate warming as a possible influence on insect populations in the Ottawa area. The other studies variously noted trends such as: an increase in wet and humid conditions (Bootsma, 1994); seasonal increases in daily minimum temperature values, as well as seasonal variation in daily maximum temperature trends (Ahmed et al, 2014); the attribution of the urban heat island effect as a cause of observed winter warming in Ottawa when contrasted with smaller surrounding communities (Prokoph and Patterson, 2004); and decreased fluvial discharge throughout the Ottawa area (Adamowski and Prokoph, 2013) and 3) trends in extreme weather.…”
Section: Introductionmentioning
confidence: 99%